A dual function of high efficiency quasi-solid-state flexible dye-sensitized solar cell based on conductive polymer integrated into poly (acrylic acid-co-carbon nanotubes) gel electrolyte. (15th May 2017) - Liu, Xianqing; Liang, Yong; Yue, Gentian; Tu, Yongguang; Zheng, Haiwu
Graphical abstract: Highlights: Quasi-solid-state flexible DSSCs. The CoS/Ag/Ti electrode showed high catalytic ability as well as Pt electrode. The novel gel electrolytes displayed significant improvement in electrochemical and photoelectrochemistry capability. The flexible DSSC with novel gel electrolytes showed significantly enhanced photovoltaic performance. Abstract: A series dual function of quasi-solid-state gel electrolytes with high conductivity and good catalytic ability were prepared by integrating the carbon nanotubes (CNTs) and conducting polymers including polypyrrole (PPy), polyaniline (PANI) and poly (3, 4-ethylenedioxythiophene) (PEDOT) into poly (acrylic acid) (PAA) gel, showing significant improvement in electrochemical and photoelectrochemistry capability used in dye-sensitized solar cells (DSSCs). These novel electrolytes provide three dimensional network structures for transporting electrons, giving a similar conduction mechanism to that of I − /I3 − liquid electrolyte system. The electrochemical performance of the CoS/Ag/Ti counter electrode (CE) was evaluated by electrochemical impedance spectroscopy, which revealed that the CoS/Ag/Ti CE exhibited excellent electrocatalytic ability for these novel electrolytes as well as that of in I − /I3 − liquid system. The quasi-solid-state flexible DSSC fabricated with the CoS/Ag/Ti CE and novel gel electrolytes integrated PPy, PANI and PEDOT achieved enhanced power conversion efficiency of 6.89%, 7.01% and 7.20% under the irradiation of 100 mW cm −2, which have much approached that of the DSSC (7.35%) based on Pt electrode and I − /I3 − liquid electrolyte.